THE BIOMIMETIC FIN PERFORMANCE EVALUATION FOR AN EFFICIENT AUTONOMOUS UNDERWATER VEHICLE (AUV) TO SUPPORT THE REVOLUTION IN MILITARY AFFAIRS (RMA) IN UNDERWATER DEFENSE - Jaya, Arie Sukma; Rukmono, Linus Yoseph Wawan (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
The world is facing the global trend of Industry 4.0 in the manufacturing sectors. The concept of the Internet of Underwater Thing (IoUT) presents the trends in the underwater region. The Autonomous Underwater Vehicle (AUV) as a data collector and transmitter becomes the central component in the connected system of the IoUT. The efficiency of the platform is crucial to lengthening the range and duration of the mission. The biomimetic method of utilizing the caudal fin propulsion could enhance the efficiency of the small and low-speed AUV. From the defense perspective, there is a concept of Revolution in Military Affairs (RMA) that supports technological modernization for defense purposes. Technically, this study aims to combine the technical aspects of mechanical engineering and the defense concept of RMA in the technological advancement of AUV for the advanced and efficient defense strategy in the underwater region. The evaluations involved numerical simulation with Computational Fluid Dynamics (CFD) method. The simulation results show that the fully tapered flexible fin enhances the efficiency by 25%, while the narrow flexible fin enhances the efficiency by 30%. These results indicate that a flexible tapered fin should be the primary consideration in designing the high-efficiency biomimetic fin. The visualization of the force vectors shows that the flexibility of the fin acts as a thrust vectoring factor that directs more force vectors in the thrust direction. This study supports the RMA concept implementation by technological modernization, such as efficient biomimetic AUV development, to develop doctrines in the State's defense in the underwater region.